Tendency Among Public And Students For The Establishment Of Islamic Waqf Bank - Muhammad Ridhwan Ab. Aziz; Yusof, Mohd Asyraf (Universiti Sains Islam Malaysia, 2024)
Islamic waqf bank is a special designed financial institution in Islam. This bank will benefit the students and also their parents, due to its unique structure that could finance student’s education in term of fees and cost of living. Islamic waqfbank uses the concept of cash waqf in term of funding the education. Cash waqf is a trust fund established with money to support services for mankind’s benefits in the name of Allah. It is recognized that there is no ample study in the area of cash waqfespecially for managing Islamic waqfbank institution. Therefore, the study for the management of cash waqffund is essential in order for the fund to be use efficiently. The objective of this paper is to examine the tendencyamong public and students for the establishment of Islamic waqf bank. The methodology of research in this paper is a quantitative research based on 210 students and 287 Muslim public.The general finding of this paper shows that there is a high tendency among public and students towards the establishment of Islamic waqf bank.